ISOLATION AND ANTIMICROBIAL RESISTANCE PHENOTYPE OF Klebsiella pneumonia FROM THE URINE OF SUSPECTED UTI PATIENTS ATTENDING PUBLIC HOSPITALS IN NASARAWA SOUTH SENATORIAL DISTRICT, NASARAWA STATE, NIGERIA - Ashefo, D. P.; Ngwai, Y. B.; Ishaleku, D. (FUDMA Journal of Sciences, 2023)
The emergence of antibiotic resistant uropathogenic Klebsiella pnuemoniae is causing major public health crisis worldwide. This study is aimed at Determining the prevalence and antimicrobial resistance phenotypes of the urinary Klebsiella pnuemoniae isolated from patients attending public hospitals in Nasarawa South Senatorial District, Nasarawa State, Nigeria. During the duration of study, urine samples of 375 patients was cultured for the presence of K. pneumonia. A loopful of urine collected in a sterile container was streaked on MacConkey Agar, CLED, and blood agar plates and incubated for 24 hours at 37°C. The identification and resistance to selected antimicrobials were processed in accordance with the approved standards. K. pnuemoniae was found in 38 of the 375 urine samples tested, resulting in an overall prevalence of 10.13%. GHO and GHK shows a lower prevalence of 4.00% each, while DASH demonstrated a higher prevalence of 14.29%. Out-patient (13.19) and females (11.88%) shows higher prevalence of K. pneumonia than in-patient (6.74%) and males (6.14%). Patients aged 25-34 had the highest prevalence (13.82%), while the age group of 54-64 had the lowest prevalence (3.57%). The bacterial isolates demonstrated more resistance to ampicillin (94.74%) and amoxicillin-clavulanic acid (73.6%) compared to cefotaxime (13.16%), ceftriazone (18.42%), ceftazidime and cefoxitin (23.60%), and gentamicin (28.94%). Thirty-three (33) distinct phenotypes were found, with the most common (7.98%) being Ampicillin (AMP), Amoxicillin-Clavulanic acid (AMT), Ciprofloxacin (CIP), Co-trimoxazole (SXT) and Streptomycin (S). The highest multiple antibiotic resistance score (31.57%) is for resistance to three antibiotics, while the lowest (2.63%) is for resistance to one,